Adi3
  • Adi3
Will Medal!!! Please help Suppose f(x) = 3x+1 and g(x) = x^2 +2x. Find x such that f(g(x)) = 10.
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
Adi3
  • Adi3
@ganeshie8
anonymous
  • anonymous
Use Wolfram alpha for this
Adi3
  • Adi3
wolfram alpha is not correct

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

DanJS
  • DanJS
replace each x value in f(x) with the entire function g(x)
DanJS
  • DanJS
f(x) = 3x+1 f(g(x)) = 3*g(x) + 1
Adi3
  • Adi3
What do you mean by that?
DanJS
  • DanJS
g(x) = x^2+2x f(g(x)) = 3*g(x) + 1 = 3 * (x^2 + 2x) + 1
DanJS
  • DanJS
see that
Adi3
  • Adi3
yeah i get it
DanJS
  • DanJS
then they tell you that equals to a value and find x
Adi3
  • Adi3
it equals 3x^2 + 6x + 1 right
DanJS
  • DanJS
10 = 3x^2 + 6x + 1
DanJS
  • DanJS
yeah the f(g(x)) does, then they tell you that is equal to 10
Adi3
  • Adi3
then how do you solve it after that, that s the part which is the most confusing for me
DanJS
  • DanJS
it is a quadratic, to get the solution, you put it in standard form first.. ax^2+bx+c=0
DanJS
  • DanJS
3x^2 + 6x - 9 = 0 3*( x^2 + 2x - 3) = 0
Adi3
  • Adi3
then what to do next
DanJS
  • DanJS
so, x^2 + 2x -3 = 0 you can always just apply the quadratic formula, but this one looks to factor easy
DanJS
  • DanJS
(x - 1)*(x+3) = 0
Adi3
  • Adi3
wait from where did x-1 come from
DanJS
  • DanJS
so, that is true if.. x - 1 = 0 OR x + 3 = 0
DanJS
  • DanJS
x = 1 or x=-3
DanJS
  • DanJS
factoring a quadratic
Adi3
  • Adi3
ohh thanks
DanJS
  • DanJS
distribute the thing and check , it goes back to the original
DanJS
  • DanJS
or simply just plug in the coefficients to the quadratic equation and hit a button to solve for you
Adi3
  • Adi3
i did not get the part after this 3x^2 + 6x - 9 = 0 3*( x^2 + 2x - 3) = 0
Adi3
  • Adi3
what did you do after this
DanJS
  • DanJS
divide both sides with a 3
DanJS
  • DanJS
0/3 = 0
DanJS
  • DanJS
Once you get down to standard form ax^2 + bx + c = 0 solving that expression for x will give you the quadratic formula
Adi3
  • Adi3
yeah i get it, thanxs
DanJS
  • DanJS
\[x = \frac{ -b \pm \sqrt{b^2 - 4*a*c} }{ 2a }\]
DanJS
  • DanJS
k, welcome
Adi3
  • Adi3
thnxs

Looking for something else?

Not the answer you are looking for? Search for more explanations.